Surgical treatment of thymic epithelial tumor and myasthenia gravis - Özçıbık Işık, Gizem; Turna, Akif (Frontiers in Surgery, 2024)
Thymic epithelial tumors originate from the epithelial cells of the thymus and are typically diagnosed during the 5th and 6th decades of life. The incidence is consistent between men and women, averaging 1.7 cases per year. Thymomas, neuroendocrine tumors, and thymic carcinomas are subtypes of thymic epithelial tumors, with thymomas being the most prevalent (75%–80%) and thymic carcinomas following at 15%–20%. Thymoma and thymic carcinoma exhibit distinct disease courses; thymomas grow slowly and are confined to the thymus, while thymic carcinomas demonstrate rapid growth and metastasis. Overall survival rates vary, with a 78% 5-year survival rate for thymoma and a 30% rate for thymic carcinoma. Thymic epithelial tumors may be linked to paraneoplastic autoimmune diseases, including myasthenia gravis, hypogammaglobulinemia, pure red cell aplasia, Cushing's syndrome, systemic lupus erythematosus, and polymyositis. Staging of thymic epithelial tumors can be done according to Masaoka-Koga and/or TNM 8th staging systems. The treatment algorithm is primarily determined by resectability, with surgery (Extended Thymectomy) serving as the foundational treatment for early-stage patients (TNM stage I-IIIA, Masaoka-Koga stage I-III). Adjuvant radiotherapy or chemotherapy may be considered following surgery. In advanced or metastatic cases, chemotherapy is the first-line treatment, followed by surgery and radiotherapy for local control. Myasthenia gravis, an autoimmune disease presents with progressive muscle fatigue and diplopia. Positive antibodies (Anti-AChR, Anti-MuSK, LRP4) and electromyography aid in diagnosis, and approximately 10% of myasthenia gravis patients can also have thymoma. Treatment includes cholinesterase inhibitors and immunotherapy agents, with extended thymectomy serving as an effective surgical option for drug-resistant cases. Minimally invasive approaches (video-assisted thoracoscopic surgery or robot-assisted thoracoscopic surgery) have demonstrated comparable oncological outcomes to sternotomy, highlighting their effectiveness and reliability.